An integrated hollow-core photonic crystal fiber transverse optical trapping system for optical manipulation and detection - Shinoj, V. K. (2013)
Optical manipulation, separation, and detection of biological cells have immense potential biomedical applications, for example, in disease detection. In this paper, we present optical manipulation and detection of micron sized fluorescent particles inside hollow-core photonic crystal fiber (HC-PCF) by transverse optical trapping. An optical trapping system is designed where a near-infrared laser light is focused using a microscope objective to create an optical trap across a liquid-filled HC-PCF. The fluorescent microsphere particles trapped in the core of HC-PCF using the laser induced optical force further undergo imaging and fluorescence spectroscopic analysis. It is illustrated that the proposed method can track the particle into a different medium using the optical trap as well. The obtained results indicate that this proposed method has tangible potential for developing HC-PCF based lab-on-a-chip bio/chemical sensors capable of detecting reagents in ultra low sample volumes.